Assessment of U.S. readiness to design, develop and produce nuclear warheads: Current status and some remedial steps. Issue 3 (26th May 2016) - Scheber, Thomas K.; Harvey, John R.
ABSTRACT: This report provides an assessment of the U.S. readiness posture to be able to design, develop, and produce new nuclear warheads or warheads with new military capabilities. Such a readiness posture is important to reduce risk over the long term for the United States and its allies. This report does not advocate any specific new nuclear capability. The focus is on a readiness capability and the steps needed to remediate a critical element of the U.S. security posture that, over the past two decades, has been documented repeatedly as being deficient. The report examines the policies of post-Cold War presidential administrations regarding maintaining a nuclear warhead design capability. In addition, it identifies capability shortfalls of the current U.S. nuclear enterprise and offers recommendations to address shortfalls—in particular, the intellectual capital on which the health of the current and future U.S. nuclear deterrent depends. Finally, it provides concrete recommendations to improve and preserve a U.S. nuclear readiness capability for the long term.